Feline idiopathic cystitis (FIC) in a mixed breed cat: case study in Malaysia - Zaini, Syamira Syazuana; Ahmad Kukri, Amir Shauqi; Othman, Azalea Hani (Universiti Putra Malaysia, 2024)
Feline idiopathic cystitis (FIC) is a common medical condition covering Feline Lower Urinary Tract Disease (FLUTD) in cats reported in many countries. However, there is a lack of prevalence studies reported in Malaysia. In this case report, a case of an FIC cat was presented at the University Veterinary Hospital, Universiti Putra Malaysia. The seven-month-old male mixed-breed cat had primary complaints of urine incontinence and haematuria. A thorough physical examination and diagnostic workup ruled out other causes, leading to the diagnosis of FIC. Based on the history provided by the owner, two weeks prior to the inappropriate urination, the cat moved into a new home, and the owner noticed that the cat appeared stressed and frequently urinated outside the litter box. In addition, the owner mentioned that dog bark noises were heard in the room where the cat was housed. Therefore, behavioural therapy (e.g., reconstitute the cat’s home environment and increase the interaction between the owner and the cat) was also conducted as part of the medical intervention in this case. The owner reported no further recurrence of clinical signs. Thus, a complete recovery was achieved with a good prognosis.